Online branding strategy for wine tourism competitiveness. Issue 2 (17th June 2019) - Scorrano, Paola; Fait, Monica; Maizza, Amedeo; Vrontis, Demetris
Abstract : Purpose: The link between wine and tourism is increasingly important for the competitive advantage of the territory and its productions, and it must be adequately communicated, in particular, online. Therefore, monitoring the level of convergence between online brand identity and online brand image is increasingly important to implement an efficient strategy of recall of a territory. This paper thus aims to propose an operative framework – assessing Web convergence (AWC) – designed to detect and analyse the online brand image and compare it with online brand identity. Design/methodology/approach: The AWC framework is designed to extract information from the Web, process it through text-mining techniques – cluster analysis – and interpret it from three perspectives – functional, holistic and sensitive. The operative framework was applied to Napa Valley because it is the most frequently cited wine destination on the top 100 travel blogs. Findings: The empirical application shows that the proposed logical framework can yield important reflections even in cases such as Napa Valley's, a destination that already enjoys strong notoriety. In spite of the apparent qualitative homogeneity of the topics discussed, observation of their composition in terms of the three dimensions revealed the existence of a gap on some topics identified between what is communicated by the wine tourism destination and what is perceived and in turn communicated by bloggers. Research limitations/implications: The limitation of the research is represented by the application of the operative process to a single case study (Napa Valley). The contribution given to managerial studies is the ability of the framework to provide an operative vision of the importance of knowing the blogger's perception of the brand identity communicated by the company. Testing the framework in other contexts will confirm that the protocol is generalisable. Practical implications: The identification of the themes that characterise brand identity and brand image in the Web provides a flow of information that, if interpreted according to the functional, holistic and sensitive perspective, transforms the themes into useful knowledge for decisional purposes. Originality/value: The managerial literature has highlighted, as in today's communication environment, a strong brand can be created and maintained by strengthening the linkage between identity and image. The proposed framework may be considered an important protocol because it allows a tourism destination to increase the flow of information on which to build or strengthen the brand identity by aligning with the brand image. This could be particularly useful for smaller and less-popular destinations.